The effect of resistance heating to the length expansion of cold bending spring steel bar - Suhaimin, Mohd Khairul Nizam (2020)
Resistance heating (RH) is a technique of heating process for metal by which the passage of an electric current passes through a conductor that produces heat. It also known as Joule Heating or Ohmic Heating. In automotive industry, RH technique has been applied in producing stabilizer bar after cold bending process as it can reduce manufacturing cost. However, the effectiveness of RH technique in this case has been questionable as number of rework case is almost 100% per production. The rework case is due to length defects of the stabilizer bar. Up to this date, there is limited study on the factors that have significant effects to RH effectiveness especially the length expansion of spring steel bar in different diameters. Hence, the aim of this study is to provide an optimum setting for significant factors of RH that can reduce the rework case in manufacturing of stabilizer bar. There are three objectives of this study. First, is to identify the significant factors that affect RH effectiveness. Second, is to analyse the effect of the significant factors of RH to the length expansion of the spring steel, and the third one is to analyse the effect of different diameter of SUP9 spring steel bars to its length expansion through resistance heating. The study opted for an exploratory study using literature study to identify the significant factor that affect RH effectiveness. A simple statistical analysis is used in identifying the significant factors. Heating temperatures and heating time have been clarified as the significant factors of RH. Design of experiment was carried out to analyse the effect of the significant factors of RH to the length expansion of spring steel bar based on the number of defects determined. The type of spring steel bar used known as spring steel of SUP9 (type code) which is a high quality cold bending spring steel that belong to the high quality carbon alloy spring steel. The result of analysis shows that small changes in heating temperature up to 20oC and heating time up to four seconds at RH process do affect the length of SUP9 spring steel bars. that had gone through cold bending process beforehand. Overall, heating temperature and heating time are the significant factors of RH that affect the expansion length of SUP9 spring steel bar which different setting is required for a range of diameter sizes for example 18mm, 20mm, 22mm, and 24mm. The result clarified that as the diameter increase, it is necessary to increase heating time by 2s for each 2mm increment of diameter. The heating temperature shall remain if the increment of diameter range within 4mm. However, the heating temperature has to be increase 10°C once the diameter change more than 4mm. The findings are valuable to automotive industry in reducing the defects due to inappropriate setting of heating temperature and heating time have been used at RH technique.